PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV B SDN 64 PEKANBARU - Usfareni '; Otang Kurniaman; Gustimal Witri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research carried out base on the lowly of the result of science in grade IV B SD Negeri 64 Pekanbaru which is from 40 students who did not complete were 24 students, meanwhile the minimal completeness criterion (KKM) stated is 70. This research is classroom action research (CAR). The purpose of this research is to improve science learning process of class IV B SD Negeri 64 Pekanbaru in academic year 2015/2016 through Quantum Teaching Model. The research was conducted into 2 cycles. Each cycle consist of two meeting and one test. The instrument used in this study is the teacher and student’s activity sheet as well as learning about the test result. This study presents an increase of average teacher’s activity in the first cycle in first meeting is 75%, the second meeting increase to 86%. The second cycle increase from 89% to 97%. Student activity based on the result of research on first cycle is from 62% in the first meeting to 79% in the second meeting. In the second cycle increase from 91% in the first meeting to 95% in the second meeting. Based on the research of students learning outcome increased from the base score 74,5 to 76,5 in the first cycle and the second cycle increase become 82,8. Based on the result of the research, it can be concluded that the implementation of Quantum Teaching Model can improve the student’s achievement in science subject of class IVB SD Negeri 64 Pekanbaru. Key words: Quantum Teaching Model, Learning Result of Science Subject